2015
DOI: 10.1080/2150704x.2015.1069903
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into uniform circular frequency diverse array (UCFDA) radars

Abstract: In the last few years, valuable research in frequency diverse arrays (FDAs) has been conducted. However, emphasis had mainly been on uniform linear arrays (ULAs) and uniform rectangular arrays (URAs). Not much attention has been devoted to other configurations. Circular symmetry of uniform circular arrays (UCAs) has been an attraction to researchers for several reasons such as the ability to scan azimuthally through 360°and better spatial resolutions. Motivated by the potential advantages of UCA, this letter p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…One can see that in both these figures, maximum is quite narrow along the angles as well as slant range. The sidelobe concentration of the proposed system in linear region is much lower than that of UFCDA proposed in [4].…”
Section: Simulations Results and Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…One can see that in both these figures, maximum is quite narrow along the angles as well as slant range. The sidelobe concentration of the proposed system in linear region is much lower than that of UFCDA proposed in [4].…”
Section: Simulations Results and Discussionmentioning
confidence: 69%
“…However, the logarithmically increasing frequency offset has been applied to linear FDA (LFDA) which fails to provide three‐dimensional (3D) target localisation and also results in beampattern with high sidelobe level concentration widely spread in the visible range. Most recent work in FDA is by Saeed et al [4] where benefits of employing frequency diversity in circular geometries have been explored; however, the work focuses on linear frequency offset.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assume a uniform circular array (UCA) composed of M omni‐directional elements with radius a as shown in Figure 2. The slant range with respect to the m ‐th element is given as [35]. rmrasinθcos(φφm), where φ is the azimuth angle, and φm=2πmM.…”
Section: Basic Fda Radar and Problem Preliminariesmentioning
confidence: 99%
“…The beam pattern analysis of planer FDA design has been presented in [122], where it was shown that planer FDA provides better directionality and higher gain when compared with conventional FDA radar. Moreover, the circular FDA geometries were deeply studied in [123], where theory, basic analysis and beam steering for uniform circular FDA was presented to get the advantages of better spatial resolutions. Moreover, non‐uniform frequency offsets based on tangent hyperbolic function were applied to this uniform circular FDA, where beam patterns of three different configurations of an FDA can be generated, just by adjusting a single function parameter of the tangent hyperbolic function in order to get enhanced system detection capability and signal‐to‐interference plus noise ratio [124].…”
Section: Fda Radarmentioning
confidence: 99%